Bone Regeneration: A Novel Osteoinductive Function of Spongostan by the Interplay between Its Nano- and Microtopography - Thomas Vordemvenne; Dirk Wähnert; Julian Koettnitz; Madlen Merten; Nadine Fokin; Andreas Becker; Björn Büker; Asaria Vogel; Daniel Kronenberg; Richard Stange; Günther Wittenberg; Johannes FW Greiner; et al. (Cells, 2020)
Scaffold materials for bone regeneration are crucial for supporting endogenous healing after accidents, infections, or tumor resection. Although beneficial impacts of microtopological or nanotopological cues in scaffold topography are commonly acknowledged, less consideration is given to the interplay between the microscale and nanoscale. Here, micropores with a 60.66 ± 24.48 µm diameter ordered by closely packed collagen fibers are identified in pre-wetted Spongostan, a clinically-approved collagen sponge. On a nanoscale level, a corrugated surface of the collagen sponge is observable, leading to the presence of 32.97 ± 1.41 nm pores. This distinct micro- and nanotopography is shown to be solely sufficient for guiding osteogenic differentiation of human stem cells in vitro. Transplantation of Spongostan into a critical-size calvarial rat bone defect further leads to fast regeneration of the lesion. However, masking the micro- and nanotopographical cues using SiO2 nanoparticles prevents bone regeneration in vivo. Therefore, we demonstrate that the identified micropores allow migration of stem cells, which are further driven towards osteogenic differentiation by scaffold nanotopography. The present findings emphasize the necessity of considering both micro- and nanotopographical cues to guide intramembranous ossification, and might provide an optimal cell- and growth-factor-free scaffold for bone regeneration in clinical settings.